Making News in India: Star News and Star Ananda - Batabyal, Somnath (Taylor and Francis, 2014)
Post-liberalisation India has witnessed a dramatic growth of the television industry as well as on-screen images of the glitz and glamour of a vibrant, 'shining' India. Through a detailed ethnographic study of Star News and Star Ananda involving interviews, observations and content analysis, this book explores the milieu of 24-hour private news channels in India today. It offers insightful glimpses into the workings of one of the mightiest news corporations in the world and its ability to manufacture everyday reality for its audiences. Based on fieldwork in Mumbai and Kolkata, this study not o
Description based upon print version of record
Keywords: Star Ananda (Television network : Kolkata, India); Star News (Television network : Mumbai, India); Electronic books; Nationalismus; Meinungsbildung; Nachrichtensendung; Indien